Willingness to pay for environmental conservation: subsidy reduction as a payment vehicle - Suziana Hassansuzi,; Raudha Md Ramli,; Naziatul Aziah Mohd Radzi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objective of the study is to test whether the subsidy reduction of daily consumer goods as a payment vehicle can influence individuals’ willingness to pay (WTP) for environmental and nature conservation. Specifically, it assessed the impact of price sensitivity on the willingness to conserve wetlands, using the subsidy reduction approach. Malaysia’s Setiu Wetland (SW) served as a case study to gauge respondents’ preferences to trade-off the benefits of subsidy with conservation of natural resources. The welfare economic concept of WTP was applied to estimate the economic value of SW with the application of choice experiment method. Analysis using the Random Parameter Logit model showed that respondent’s WTP for conserving SW, through subsidies reduction, amount to RM120.59 annually. The price sensitivity in the model is high, suggesting that respondents are greatly concerned about the monetary attribute. This further implies that subsidy reduction can be a most consequential and coercive payment for Stated Preference studies. Thorough assessment of the payment structure is crucial for the quality of environmental value research in developing economies when conventional methods may not be ideal. It is recommended that policymakers consider other alternatives as payment vehicles for environmental conservation to ensure broader support for conservation initiatives.